Alterações maxilofaciais em crianças com síndrome da zika congênita - PINHEIRO, Ana Carolina Mendes (2020)
The similar embryological origin between the maxillofacial and dental structures, and those of the nervous tissue, which the Zika virus has special tropism, indicates that the Congenital Zika Syndrome (SZC) may be related to the presence of orofacial changes. The formation of these structures begins in intrauterine life, and their changes provide clues about the timing and nature of pre and postnatal triggering factors. This work aims to compare the orofacial characteristics of children with Congenital Zika Syndrome (CZS) infected at different times of pregnancy. This is a cross-sectional study, between October 2016 and July 2019, in the state of Maranhão, carried out in children with SZC, divided into two groups: mothers infected in the 1st trimester (n = 56), and those infected in the 2nd and 3rd trimesters (n = 52). The children were sent to the NINAR Support House. Socioeconomic, maternal and child health data were chosen from medical records and named. Dental data were collected through visual examination of orofacial structures. The characterization of the groups was performed using mean, standard deviation, absolute and relative frequencies. To assess statistical differences, the chi-square test was classified. The mean age of children infected in the 1st trimester was 31 (±8.8) months, and children infected in the 2nd/3rd trimester of 33 (±7.2) months. The prevalence of maxillofacial changes was 7.6 cases/10 children in the group infected in the 1st trimester, and 6.9 cases/10 children among those infected in the 2nd/3rd trimester. Two cases of cleft lip and palate were observed in children infected in the 1st trimester. 17.86% and 11.54% of children infected in the 1st and 2nd/3rd trimester, respectively, alternative lingual frenulum alteration. The most common dental alteration was Opacity, in both groups. Although there is no necessary difference regarding the period of infection during pregnancy, children infected in the first trimester have a higher prevalence of orofacial changes compared to those infected in the second and thrid trimester.